Congenital pseudarthrosis of the tibia: The results of an evolving protocol of management. (October 2013) - Nicolaou, N.; Ghassemi, A.; Hill, R. A.
Abstract: Purpose: This retrospective cohort study assesses the outcomes of a protocol of management, based on the recommendations of the European Paediatric Orthopaedic Society (EPOS) multi-centre study, for the management of congenital pseudarthrosis of the tibia. Methods: Utilising an incremental protocol of bracing, intramedullary rods and circular frame fixation with or without bone morphogenetic protein-2 (BMP-2), 11 patients had reached skeletal maturity or had follow up of 5 years from radiological union of the pseudarthrosis. Demographic data, deformity parameters before and after treatment, and functional outcome scores were recorded. Results: Ten of the 11 patients successfully healed and two sustained a refracture. All deformity parameters improved and a mean leg length discrepancy of 2.5 cm (range 0–7.5 cm) existed at the time of the last follow up. Some pseudarthroses healed with deformity correction and rod insertion alone. Six of the 11 patients had a confirmed diagnosis of neurofibromatosis and nine had sustained a fracture before 4 years of age. Refracture was associated with malalignment after healing. Conclusion: This method of treatment provides a successful stepwise protocol for the management of this complex disorder, avoiding the use of aggressive limb reconstruction techniques at a young age in some cases. Level of evidence: Case series Level IV.